Kemampuan Ekstrak Galaktomanan dari Ampas Kelapa dalam Menstimulasi Pertumbuhan Bakteri Asam Laktat - Sitanggang, Fitra Ayu; Antara, Nyoman Semadi; Gunam, Ida Bagus Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 1 (2022): Maret, 2022)
This study aimed to determine the ability of galactomannan extract from coconut pulp to stimulate the growth of lactic acid bacteria and to determine the concentration of galactomannan from coconut pulp that could stimulate the growth of lactic acid bacteria with the best growth rate. The experiment was conducted in vitro where the growth medium used was MRS Broth without glucose but added with galactomannan from coconut pulp. MRS Broth media with glucose was used as a control with a concentration of 1%. The galactomannan concentrations used were 0%, 0.5%, 1%, 1.5%, and 2% (w/v). Determination of the confirmed time was carried out by measuring the optical density (OD) on 1.5% galactomannan extract media once every 3 hours. The results showed that galactomannan from coconut pulp can stimulate the growth of lactic acid bacteria. Total lactic acid bacteria related to the degree of acidity and total acid. The more total bacteria, the lower the pH value, thus the total acid will increase. In the media that was added galactomannan from coconut pulp, the best total lactic acid bacteria, pH and total acid were obtained from a concentration of 1% (w/v) with 9 hours incubation, the highest total lactic acid bacteria was 4,5 CFU/mL . Keywords: Coconut pulp, galactomannan, lactic acid bacteria